Multiple communication mechanisms between sensor kinases are crucial for virulence in Pseudomonas aeruginosa - Francis, Vanessa I.; Waters, Elaine M.; Finton-James, Sutharsan E.; Gori, Andrea; Kadioglu, Aras; Brown, Alan R.; Porter, Steven L. (Nature communications, 2018)
Bacteria and many non-metazoan Eukaryotes respond to stresses and threats using two-component systems (TCSs) comprising sensor kinases (SKs) and response regulators (RRs). Multikinase networks, where multiple SKs work together, detect and integrate different signals to control important lifestyle decisions such as sporulation and virulence. Here, we study interactions between two SKs from Pseudomonas aeruginosa , GacS and RetS, which control the switch between acute and chronic virulence. We demonstrate three mechanisms by which RetS attenuates GacS signalling: RetS takes phosphoryl groups from GacS-P; RetS has transmitter phosphatase activity against the receiver domain of GacS-P; and RetS inhibits GacS autophosphorylation. These mechanisms play important roles in vivo and during infection, and exemplify an unprecedented degree of signal processing by SKs that may be exploited in other multikinase networks. Bacteria respond to stresses using two-component systems consisting of sensor kinases (SKs) and response regulators. Here, Francis et al . reveal three specific interaction mechanisms between a pair of SKs that are important for regulation of virulence in the pathogen Pseudomonas aeruginosa .